The impact of file sharing based on the peer-to-peer technology - Raja Shaharuddin, Raja Aida (Universiti Teknologi Malaysia, 2002)
The development of ICT had enabled file sharing to be implemented easily. The file sharing technology is being developed due to the vast growth of information. However, there are some drawbacks such as data collision, file copying, security and others. This paper focuses precisely on the Peer-To-Peer File Sharing Technology that includes Napster Architecture and GNUTELLA Architecture. This also, to show how Napster Architecture violates the copyright law and how GNUTELLA Architecture manages to outbeat the law. However, there are questions that we need to think about such as how secure you are in the Peer-To-Peer File Sharing Technology?